Design of a microstrip patch sensor antenna for the measurement of permittivity. (2021) - Islam, Mohammad Tawsiful; Islam, Sikder Sunbeam; Rocky, Abu Sajed; Alam, Asraful; Chy, Mehidi Hossen; Faruque, Mohammad Rashed Iqbal
Abstract: This paper presents a new high gain Microstrip Patch Sensor Antenna for the measurement of permittivity. The proposed antenna uses a copper (annealed) patch imposed over the FR-4 substrate. Here several thin rectangular slots are loaded along the radiation side and two circular slots in the mid of the patch. The constructed design offers Return loss = −29.13 dB, Gain = 6.26 dBi at resonant frequency 2.33 GHz. This proposed antenna is aimed to increase the sensitivity by measuring the permittivity of material and is also employed for wireless application. The design also shows a non-linear frequency shift with the change of relative permittivity of the Material Under Test (MUT). Computer simulation technology software (CST) has been used to execute this design, simulation, and perform analysis. The proposed antenna can be employed for measuring humidity, Salinity determination of seawater, temperature, and other characteristics simultaneously. This antenna is expected for measuring permittivity for both solid and liquid materials.